Transformasi Pemikiran Muhammadiyah Dari Puritanisme Ke Kosmopolitanisme - Syafrianto, Syafrianto; Apris, Apris; Mursal, Mursal; Lahmi, Ahmad (Institut Agama Islam Sumatera Barat, 2024)
This research aims to explore the development and transformation of Muhammadiyah thought from puritanism to cosmopolitanism. This research uses a qualitative method with a library research model. The source of data for this research is by searching for books and scientific articles in online journals with the help of the Publish or Perish application and Google Scholar. After the data is found, it is filtered and classified according to the theme discussed. Furthermore, the author will present the results of the research in the form of narratives and graphs, making it easier to understand the discussion. The results of this research can be concluded, that Muhammadiyah as a modernist Islamic movement, is rooted in the spirit of puritanism which emphasises the purification of Islamic teachings based on sacred texts and practices of the salaf generation. Over time, the organisation underwent a transformation towards cosmopolitanism, which integrates inclusive, adaptive, and universal values. This shift was influenced by globalisation, the dynamics of science, and contextual needs, which encouraged Muhammadiyah to combine puritanism with tajdid (renewal). Through the concept of Islam Berkemajuan, Muhammadiyah carries the vision of universal humanitarian solidarity, dialogue between civilizations, and active participation in global issues. This transformation reflects a shift from a doctrine-based movement to one that contributes significantly to the welfare of humanity, maintaining relevance at the national level, while expanding its influence on the global stage.